Max Weber’s Methodology and the Comparative Sociology of Religion - Eliæson, Sven (Revue internationale de philosophie, 2016)
Max Weber’s methodology is often treated by some as his principal contribution to social science, while his comparative sociology of religion starting with the famous Calvinist thesis is the Schwerpunkt in his work, according to others. There are several reasons to locate and analyze the conjunctions between these two interpretations. Weber’s ideal type is formulated in several places, not only in the so-called ‘Objectivity’ essay from 1904, but also for instance in the marginal utility-essay from 1908. His three meta-texts for the three volumes in GARS (Gesammelte Aufsätze zur Religionssoziologie) are also illuminating, especially in ‘Einleitung’ (‘Introduction’) and ‘Zwischenbetrachtung’ (or ‘Intermediate Reflections’). It was in the ‘Zwischenbetrachtung’ where he commented on religion in India, partly as an ‘identity giving other’, that the ideal type reappeared. Weber deals with the uniqueness of Occidental culture and his comparative religion serves as supporting evidence, much in line with J S Mill’s canons for the logic of isolating independent variables by similarities and differences -as indicated in a letter by Weber to Georg von Below. As a result Weber serves still today as a sparring partner for theorists of the Axial Age and the multi-modernity paradigm.